Messages From the Past: New Insights in Plant Lectin Evolution - Van Holle, Sofie; Van Damme, Els J. M. (Frontiers in Plant Science, 2019)
Lectins are a large and diverse class of proteins, found in all kingdoms of life. Plants are known to express different types of carbohydrate-binding proteins, each containing at least one particular lectin domain which enables them to specifically recognize and bind carbohydrate structures. The group of plant lectins is heterogeneous in terms of structure, biological activity and function. Lectins control various aspects of plant development and defense. Some lectins facilitate recognition of exogenous danger signals or play a role in endogenous signaling pathways, while others are considered as storage proteins or involved in symbiotic relationships. In this study, we revisit the origin of the different plant lectin families in view of the recently reshaped tree of life. Due to new genomic sampling of previously unknown microbial lineages, the tree of life has expanded and was reshaped multiple times. In addition, more plant genomes especially from basal Phragmoplastophyta, bryophytes and Salviniales (e.g. Chara braunii, Marchantia polymorpha, Physcomitrella patens, Azolla filiculoides and Salvinia cucullata) have been analyzed, and annotated genome sequences have become accessible. We searched 38 plant genome sequences including core eudicots, monocots, gymnosperms, fern, lycophytes, bryophytes, charophytes, chlorophytes, glaucophytes and rhodophytes for lectin motifs, performed an extensive comparative analysis of lectin domain architectures, and determined the phylogenetic and evolutionary history of lectins in the plant lineage. In conclusion, we describe the conservation of particular domains in plant lectin sequences obtained from algae to higher plants. The strong conservation of several lectin motifs highlights their significance for plants.